The roles of administrators in distance learning programme at higher learning institutions - Hashim, Che Noraini; Kazeem, Bakare; Syed Hassan, Sharifah Sariah (2014)
—This study examined the role of administrators in facilitating instructors and students of distance education programme (DEP) to the use of effective communication tools of the present digitized environment. Administrators/coordinators of DEP were purposively selected from three different universities in Malaysia. Their responses from interviews had been transcribed and coded. Students' feedback and monitoring activities on Learning Management System (LMS) were also collected and analyzed. Findings suggest that administrators did not consider certificate or experience in distance learning while recruiting instructors to teach in DEP. Instead, they perceived that university lecturers from the conventional programme should be able to fulfil course learning outcomes designed for the DEP. Evidence had shown that administrators bureaucratic decision in mandating LMS with grade attached, seemed to deter lecturers from using effective communication tools such as emails and facebook. When asked on plans to improve the administration of DEP, the administrators mentioned that training has really helped lecturers to improve their content delivery skills. It is concluded that the circumstantial or semester training through LMS which involved training among lecturers who are new in the e-learning environment is inadequate. The monitoring of DEP through the LMS is recommended to be focused on upgrading communication practices as well as attitudes among lecturers for effective online instructions which are critical to the eventual achievement of the DEP learners.